Lifelong learning processes in professional development for online teachers during the Covid era - Reychav, Iris; Elyakim, Nitzan; McHaney, Roger (Frontiers in Education, 2023)
Introduction Lifelong learning encompasses four pillars: (1) learning to know; (2) learning to do; (3) learning to be; and (4) learning to live together. These four pillars, which are expanded upon within the current study provide a lens to examine relationships between professional development, use of technology for remote online teaching, and pedagogical efficacy in the age of COVID-19. Methods The study examined survey responses from 372 primary school subjects representing six different districts, and interviews with 16 teachers. The responses were analyzed using correlation and MANOVA statistical tests. Results Teachers’ professional development processes were found to have a positive impact on the teachers’ pedagogical efficacy, by means of positive perceptions toward the use of technology for remote online teaching. Learning foci predicted the use of technology, and the use of technology predicted learning assessment measurements. Discussion The study’s findings reinforce the need for professional development processes based on systematic identification of pedagogical needs that arise in the field, their analysis and the understanding of the added value of pedagogical tools that can support enhanced implementation of teaching - learning - evaluation. The study’s findings point to epistemological elements related to the types of acquired knowledge and to learning methods, which make it possible to differentiate between various processes in teachers’ professional development as well as processes in the use of innovative pedagogical technology.